2000
DOI: 10.4049/jimmunol.164.8.3990
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of the Antibody Response to IgE/Antigen Complexes in CD23-Deficient Mice by CD23+ Spleen or Bone Marrow Cells

Abstract: Mice immunized with IgE/Ag complexes produce significantly more Ag-specific Abs than mice immunized with Ag alone. The enhancement is mediated via the low-affinity receptor for IgE (FcεRII or CD23), as shown by its complete absence in mice pretreated with mAbs specific for CD23 and in CD23-deficient mice. Because the constitutive expression of murine CD23 is limited to B cells and follicular dendritic cells (FDCs), one of these cell types is likely to be involved. One of the suggested modes of action of IgE/CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 41 publications
(30 reference statements)
3
48
0
Order By: Relevance
“…9 and 19) as well as the ability to enhance Ab responses (9,19) are similar after immunization with IgE-and IgG2a-complexed Ag; the two Ab classes clearly use different mechanisms to achieve these effects. As described previously, IgE is dependent on CD23 expressed on B cells (18,19) and IgG2a requires activating Fc␥Rs expressed on a bone marrow-derived cell other than the B cell (which lacks activating Fc␥Rs) (7)(8)(9). Another difference, first described herein, is that IgG2a-Ag complexes are not transported as rapidly into the follicles as IgE-Ag complexes (Fig.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…9 and 19) as well as the ability to enhance Ab responses (9,19) are similar after immunization with IgE-and IgG2a-complexed Ag; the two Ab classes clearly use different mechanisms to achieve these effects. As described previously, IgE is dependent on CD23 expressed on B cells (18,19) and IgG2a requires activating Fc␥Rs expressed on a bone marrow-derived cell other than the B cell (which lacks activating Fc␥Rs) (7)(8)(9). Another difference, first described herein, is that IgG2a-Ag complexes are not transported as rapidly into the follicles as IgE-Ag complexes (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…The only murine hematopoietic cells expressing CD23 are B cells and FDCs (20 -22). Since CD23 expression on B cells, but not on FDCs, is required for IgE-mediated enhancement (18,19), a mechanism involving transfer of IgE/Ag from FO B cells to FDCs, as shown to take place with IgM-and IgG-immune complexes (37,43) mechanism is CD23 dependent. Especially when using EBV-transformed B cell lines, which should be free of contaminating cell types, contribution of DCs to the T cell stimulation/Ag presentation is excluded (26 -28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, IgE-Ag complexes may be captured by CD23 expressed on FDC and presented efficiently to B cells as immune complex-coated bodies, iccosomes. However, this is unlikely because chimeric mice, with CD23 ϩ FDC and CD23 Ϫ bone marrow (BM)-derived cells, are unresponsive to IgE-Ag complexes whereas mice with CD23 Ϫ FDC and CD23 ϩ BM-derived cells do respond (32). Because FDC and B cells are the only cell types proven to express the murine CD23a isoform in vivo (21,22), the lack of a role for FDC implies that the B cells are the effector cells.…”
Section: Ige Enhances Antibody and T Cell Responsesmentioning
confidence: 99%
“…Work done in CD23-deficient animals showed that the absence of CD23 resulted in no enhancement of Ag-specific IgG when these mice were injected with IgE anti-hapten/hapten-Ag complexes (45). More recently, Heyman et al (46) published that it is the CD23 on B cells that is responsible for the enhancement of IgE-mediated Ag presentation. Interestingly, mice treated with RAS1 produce less Ag-specific IgG1 than control animals.…”
Section: Figurementioning
confidence: 99%